FORMULASI SEDIAAN ORALLY DISINTEGRATING TABLET ATENOLOL DENGAN SODIUM STARCH GLYCOLATE SEBAGAI SUPERDISINTEGRAN - Karina Citra Rani; Nani Parfati; Jessica Wangsa Putri (Sanata Dharma University, 2017)
Atenolol, a competitive beta (1)-selective adrenergic antagonists, has been widely used in hypertension therapy. Administration of conventional tablets of atenolol has limitation due to patient compliance in geriatric patients. Formulation of atenolol as orally disintegrating tablet (ODT) can improve the effectiveness of the drug and patient compliance in hypertension therapy. The objective of this study was to formulate orally disintegrating tablet of atenolol using sodium starch glycolate as superdisintegrant in two different concentrations (10% and 20%). Orally disintegrating tablets (ODT) of atenolol without superdisintegrant were used as a control in this study. It was found that orally disintegrating tablets (ODT) of atenolol which used 10% sodium starch glycolate have better wetting time (9.330.58 seconds), disintegration time (15.481.16 seconds), in vitro dispersion time (24.001.00 seconds), and dissolution efficiency (95.230.14 %) than orally disintegrating tablet (ODT) which used 20% sodium starch glycolate.